Best proximity point theorems for g-proximal weak contractions in complete metric spaces endowed with graphs - Chalongchai Klanarong (2018)
© 2018, SINUS Association. All rights reserved. In this paper, the existence of best proximity point theorems for two new types of nonlinear non-self mappings in a complete metric space endowed with a directed graph are established. Our main results extend and generalize many known results in the literatures. As a special case of the main results, the best proximity point theorems on partially ordered sets are obtained.